2015
DOI: 10.1021/acs.jpca.5b07468
|View full text |Cite
|
Sign up to set email alerts
|

Products and Mechanism of the Reaction of 1-Pentadecene with NO3 Radicals and the Effect of a −ONO2 Group on Alkoxy Radical Decomposition

Abstract: The linear C15 alkene, 1-pentadecene, was reacted with NO3 radicals in a Teflon environmental chamber and yields of secondary organic aerosol (SOA) and particulate β-hydroxynitrates, β-carbonylnitrates, and organic peroxides (β-nitrooxyhydroperoxides + dinitrooxyperoxides) were quantified using a variety of methods. Reaction occurs almost solely by addition of NO3 to the C═C double bond and measured yields of β-hydroxynitrate isomers indicate that 92% of addition occurs at the terminal carbon. Molar yields of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 73 publications
1
35
1
Order By: Relevance
“…The current set of experimental and theoretical data is in disagreement with the experimental data by Yeh et al, 18 who concluded that the decomposition and isomerisation of aliphatic nitrate-RO have comparable rates, and that the alkoxy radicals SARs by Vereecken and Peeters 13,59 thus strongly underestimate the rate of decomposition relative to isomerisation. Our current set of high-level theoretical results still finds that decomposition is slower, and that isomerisation dominates over decomposition, in agreement with the original SARs.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…The current set of experimental and theoretical data is in disagreement with the experimental data by Yeh et al, 18 who concluded that the decomposition and isomerisation of aliphatic nitrate-RO have comparable rates, and that the alkoxy radicals SARs by Vereecken and Peeters 13,59 thus strongly underestimate the rate of decomposition relative to isomerisation. Our current set of high-level theoretical results still finds that decomposition is slower, and that isomerisation dominates over decomposition, in agreement with the original SARs.…”
Section: Discussioncontrasting
confidence: 94%
“…They propose that the decomposition SAR by Vereecken and Peeters 13 is incorrect, overestimating the barrier heights for b-ONO 2 -substituted alkoxy radicals by B3.7 kcal mol À1 ; this reduction in barrier height would allow decomposition to be competitive against H-migration as predicted by the SAR by Vereecken and Peeters. 59 The current theoretical results remain in clear disagreement with the result of Yeh et al 18 The higher-level calculations presented in this work support the barrier heights for decomposition predicted by the SAR by Vereecken and Peeters, 13 and even find that they should be slightly higher than the predictions by this SAR for 1-ONO 2 -2-pentadecoxy. While we did not examine pentadecene-derived alkoxy radicals directly due to the computational cost, the H-migration rates in 1-pentene and 2-hexenederived nitrate-RO remain in agreement with the H-migration SAR by Vereecken and Peeters, 59 dominating over the decomposition by several orders of magnitude.…”
Section: Comparison To Literature Experimental Datasupporting
confidence: 38%
See 3 more Smart Citations